The prevalence and performance of resistance exercise training activities in an Australian population in relation to health authority guidelines. Issue 6 (June 2018) - Humphries, Brendan; Stanton, Rob; Scanlan, Aaron; Duncan, Mitch J.
Abstract: Objectives: Resistance training research highlights the importance of training intensity to resistance exercise training (RET) and the associated benefits to health and function for healthy and at-risk populations. The American College of Sports Medicine (ACSM) recommend specific intensities, frequencies, repetitions, and number of exercises of RET to be performed to maintain health. The primary aim of this study was to describe the prevalence of achieving recommended levels of RET in relation to ACSM guidelines for intensity, frequency, repetitions, and number of exercises in a regional Australian population. Design: A Computer-Assisted-Telephone-Interview (CATI) survey (n = 1237) was conducted to determine RET participation. Methods: Participants were 18 years plus, residing in Central Queensland, Australia. Results: The prevalence of respondents performing 'No RET', 'insufficient RET' and 'sufficient RET' were 79.6.0%, 15.2% and 5.2% respectively. Significantly higher proportions of younger adults adhered to all RET guidelines for intensity (19.2 vs 8.1%), frequency (19.9 vs 11.6%), repetitions (17.8 vs 6.3%), and number of exercises (8.2 vs 3.6%) (p < 0.05). Significantly higher proportions of males, younger adults (18–34 years), higher educated individuals (> 15 years), and individuals engaging in sufficient levels of aerobic exercise training (AET) engaged in sufficient levels of RET (p < 0.05). Conclusions: The prevalence of Australian's participating in regular RET programs is low and only a small proportion of participants meet ACSM guidelines for the quantity and quality of RET that is likely to provide health benefits. This has implications for public health policy and the future development and promotion of population-level RET guidelines.